Intra-articular hyaluronic acid for treatment of osteoarthritis: a nationwide study among the older population of Taiwan - Chen Tzeng-Ji (BMC Health Services Research, 2008)
Abstract Background Although intra-articular treatment with hyaluronic acid (HA) for symptomatic osteoarthritis has become widely accepted in recent decades, the pattern of its use has seldom been reported. We have explored the epidemiology of intra-articular HA treatment in Taiwan by using the rich data source from nationwide insurance claims. Methods Taiwan's National Health Insurance (NHI), which covers 97% of inhabitants, offers extensive hospitalisation and ambulatory care. We identified the beneficiaries aged 60 years and older who received intra-articular HA within the NHI during 2004. The number of visits in which HA was administered were analysed by patient's age and gender and by the physician's specialty and practice site. Results Among the 73,410,777 ambulatory visits by 2,909,219 beneficiaries aged 60 years and older in 2004, 35,782 (1.2%) patients received intra-articular HA treatment in 205,012 (0.3%) visits. The highest prevalence of HA use was in the 70–79 year age group in both sexes. Women received intra-articular HA treatment more frequently than men in all age groups, especially in the 60–69 and 70–79 year groups (1.6% vs. 0.5%, 2.2% vs. 1.0%, respectively). Most intra-articular HA procedures were performed by orthopaedic surgeons (75.1%) and physical medicine and rehabilitation physicians (15.2%), and at metropolitan hospitals (34.5%) and local community hospitals (38.2%). Conclusion One out of 100 older patients in Taiwan received intra-articular HA treatment for osteoarthritis of the knee during the course of the year. There were age-gender differences in use of HA treatment. The completion rate of this treatment in our study was high, and thus intra-articular HA might be a good alternative for patients for whom conventional treatment fails. Further research is needed to examine the age-gender differences in use of intra-articular HA in Taiwan.